Analysis of Factors Influencing Nutritional Status of Children Under Five Year Old - Inaya Nur Aini; Isah Fitriani; Tri Budi Rahayu (Journal of Public Health Indonesian, 2026)
Nutritional status of children under five is a key indicator of public health and reflects the quality of human resource development. Malnutrition among under-five children remains prevalent in many communities and is influenced by multifactorial determinants. This study aimed to analyze factors influencing the nutritional status of children under five using a quantitative analytic approach. An observational analytic study with a cross-sectional design was conducted involving 240 children and their mothers or caregivers. Data were collected using anthropometric measurements and structured questionnaires. Bivariate and multivariate analyses were performed using logistic regression. The results revealed that household socioeconomic status, feeding practices, maternal education, and sanitation conditions were significantly associated with children’s nutritional status. Multivariate analysis identified household socioeconomic status as the most dominant factor affecting nutritional status, followed by feeding practices and maternal education. These findings indicate that child malnutrition is not solely related to individual behavioral factors but is also strongly influenced by broader socioeconomic and environmental conditions. This study highlights the need for integrated, community-based, and evidence-driven nutrition interventions that address social, economic, and environmental determinants simultaneously.